Proses Pemilihan Alternatif Kebijakan Daerah : Studi Kasus tentang Komite Ekonomi Kreatif - Sri Iwandari Putri; Alizar Isna; Slamet Rosyadi (Jurnal Ilmu Administrasi Negara ASIAN (Asosiasi Ilmuwan Administrasi Negara), 2020)
The Banyumas Regency government intends to develop the potential of economy creative in their region through the Banyumas Regent Decree No.050/462/Year 2018 about creative economy committee. In connection with the stipulation of the policy, was reviewed the process of selecting the Banyumas Regent Decree Number 050/462/Year 2018 concerning Banyumas Creative Economy Committee as a regional policy, the election of the Banyumas Regent Decree Number 050/ 462/Year 2018 concerning the Banyumas Creative Economy Committee based on criteria technical feasibility; political viability; economic and financial possibility; and administrative operability, and to find out whether there are other criteria used by the Banyumas Regency Government when determining the Banyumas Regent Decree Number 050/462/Year 2018. The research method used in this study is a qualitative method. The selection of informants uses purposive sampling and snowball sampling. Data is collected through in-depth interviews, observation and documentation. The data analysis method used is an interactive analysis method. To accomplish the validity of the data, the criteria for the degree of trust, transferability, dependability and certainty were used. The results showed that the alternative policy was chosen based on the criteria for selecting the alternative policy: 1) Technical feasibility, it was found that the purpose of establishing KEK was as a forum for ecraf’s actors. 2) Economic and financial, KEK doesn’t receive any special funds and no goals have been achieved. 3) Political viability, this policy doesn’t contradicting with the applicable regulations. 4) Administrative Operability policy is realistic, but the support from the nine offices has not been maximal. 5) The criteria chosen are based on the success of the other regions and then it is adopted. It is the main criteria in the process of selecting and determining KEK as an alternative policy for the development of creative economy potentian in Banyumas Regency